Relationship of Urologic Complications With Health-Related Quality of Life and Perceived Value of Health in Men and Women With Type 1 Diabetes: The Diabetes Control and Complications Trial/Epidemiology of Interventions and Complications (DCCT/EDIC) Cohort - Jacobson, Alan M. (Diabetes Care, 2015)
OBJECTIVE: Limited information exists about the influence of urologic complications on health-related quality of life (HRQOL) in patients with type 1 diabetes. RESEARCH DESIGN AND METHODS: We studied 664 men and 580 women from the Diabetes Control and Complications Trial/Epidemiology of Interventions and Complications Study: mean ages were 51.6 ± 6.6 and 50.6 ± 7.2 years and duration of diabetes was 29.5 ± 4.8 and 29.8 ± 5.1 years, respectively. We assessed associations of sexual dysfunction, lower urinary tract symptoms (LUTS), and, in women, urinary incontinence (UI) with general quality of life (SF-36), perceived value of health (EuroQol-5), diabetes-related quality of life (Diabetes Quality of Life Scale [DQOL]), and psychiatric symptoms (Symptom Checklist 90-R). RESULTS: In both men and women, urologic complications adversely affected HRQOL and psychiatric symptoms, even after accounting for history of depression leading to treatment. Multivariable analyses accounting for the presence of diabetic retinopathy, neuropathy, and nephropathy also revealed substantial independent effects. In men, for example, the odds (95% CI) of a low DQOL score (≤25th percentile) were 3.01 (1.90–4.75) times greater with erectile dysfunction and 2.65 (1.68–4.18) times greater with LUTS and in women, 2.04 (1.25–3.35) times greater with sexual dysfunction and 2.71 (1.72–4.27) times greater with UI/LUTS combined compared with men and women without such complications. Similar effects were observed for the other measures. CONCLUSIONS: Sexual dysfunction and urinary complications with type 1 diabetes are associated with decreased quality of life and perceived value of health and with higher levels of psychiatric symptoms, even after accounting for other diabetes complications and depression treatment.